ALTERNATIVE FORMS OF TOURISM AS A STRATEGIC SOLUTION FOR THE PROBLEM-SHORT TOURISM SEASON IN THE REPUBLIC OF MACEDONIA - Iliev, Dejan; Mijalov, Risto; Kitevski, Goran (MACEDONIAN GEOGRAPHICAL SOCIETY, 2015)
The main feature of the tourist movements in the country of Republic of Macedonia is the seasonal concentration which occurs as a result primarily of the needs of tourists for leisure and recreation in coastal areas of the natural lakes in the summer and mountain centers during the winter months. Thus, Republic of Macedonia is an interesting destination for tourists during the summer months of July and August and in a very small part of the winter tourist season, while in spatial aspect, most attractive places are Ohrid and Skopje. This distribution of temporal and spatial concentration of tourist movements causes a range of substantive issues like the short tourist season, unprofitably performance of the tourism sector and so on. The way out of this situation should be sought in the discovery and activation of new tourism places outside the main summer and winter fraction of the tourist season, or through the process of planning, organizing and developing alternative forms of tourism (congress, cultural tourism, rural tourism, spa tourism, hunting tourism etc.) for which, the Republic of Macedonia has a quality potential, but so far has not been sufficiently exploited.
Keywords: alternative tourism, seasonal concentration tourism, tourist movements, tourist turnover